Facile Fabrication of Redox-Active Covalent Organic Frameworks via Reductive N -methylation - Jinquan Suo; Fengqian Chen; Bin Zhao; Hui Li; Valentin Valtchev; Shilun Qiu; Qianrong Fang (Journal of the American Chemical Society, 2026)
Abstract Redox-active covalent organic frameworks (COFs) are promising materials for electronics, sensing, and catalysis. However, their synthesis is hampered by the scarcity of redox-active monomers and the difficulty of functionalizing as-synthesized frameworks without compromising crystallinity. Here, we introduce a reductive N-methylation strategy that enables the universal and mild conversion of imine-linked COFs into crystalline tertiary amine-linked frameworks (NMe-COFs). The method preserves structural order while imparting strong electron-donating and redox-responsive properties. Among the NMe-COFs, COF-300-NMe exhibits an 11-fold increase in iodine uptake with a distinct gate-opening adsorption profile─a behavior that computational studies attribute to enhanced framework flexibility and raised electronic energy levels. Furthermore, incorporation of the electron acceptor 7,7,8,8-tetracyanoquinodimethane into COF-300-NMe yields a charge-transfer complex exhibiting distinct spin signatures. This work establishes a versatile postsynthetic linkage conversion strategy, paving the way toward stimuli-responsive soft COFs and purely organic spin-active materials.